Differences in Postnatal Growth of Preterm Infants in Northern China Compared to the INTERGROWTH-21st Preterm Postnatal Growth Standards: A Retrospective Cohort Study - Zhang, Li; Gao, Nan-Nan; Liu, Hui-Juan; Wu, Qiong; Liu, Ju; Zhang, Ting; Sun, Jin; Qi, Jian-Hong; Qiao, Xiu-Yun; Zhao, Yan; Li, Yan (Frontiers in Pediatrics, 2022)
Background: The INTERGROWTH-21st preterm postnatal growth standards (IPPGS) have increasingly been used to evaluate the growth of preterm infants worldwide. However, the validity of IPPGS application to specific preterm populations remains controversial. This retrospective cohort study aimed to formulate reference growth charts for a preterm cohort in northern China and compare to the IPPGS. Methods: A total of 1,827 healthy preterm infants with follow-up visits before 70 weeks postmenstrual age (PMA) were retrospectively sampled from a preterm cohort (N=2011) born between January 1, 2011 and February 28, 2021 at the First Affiliated Hospital of Shandong First Medical University. Using the Generalized Additive Models for Location, Scale, and Shape method, 5539 sets of longitudinal data were used to construct percentile and Z-score charts of length, weight, and head circumference (HC) at 40–64 weeks PMA. Z-scores of length, weight, and HC (LAZ, WAZ, and HCZ) before 64 weeks were calculated using the IPPGS. Differences in the 50th percentile values between preterm infants and IPPGS (dLength, dWeight, and dHC) were calculated. Z-scores were assigned to six PMA clusters: 40–44, 44–48, 48–52, 52–56, 56–60, and 60–64 weeks for comparison between sexes. Results: For eligible infants, the mean PMA and weight at birth were 33.93 weeks and 2.3 kg, respectively. Boys, late preterm infants, twins, and infants with exclusively breastfeeding accounted for 55.8%, 70.6%, 27.8%, and 45.9%, respectively. Compared to IPPGS, preterm infants were longer and heavier, especially for dLength in girls (range, 2.19–2.97 cm), which almost spanned the 50th and 90th percentiles of IPPGS. The dHC tended to narrow with PMA for both sexes. The mean LAZ, WAZ, and HCZ of both sexes at all PMA clusters were >0, especially for LAZ and WAZ (about 1.0 relative to IPPGS), indicating higher levels than IPPGS at 40–64 weeks. Girls had larger LAZ at each PMA cluster, larger WAZ at 40–44 weeks, and lower HCZ after 56 weeks than boys. HCZ declined with PMA for both sexes. Conclusion: Postnatal growth of this preterm cohort was considerable higher than that of the IPPGS at 40–64 weeks PMA with sex differences.